2022
DOI: 10.22207/jpam.16.spl1.04
|View full text |Cite
|
Sign up to set email alerts
|

Computational Purposing Phytochemicals against Cysteine Protease of Monkeypox Virus: An In-silico Approach

Abstract: The development and evolution of viruses that cause disease have presented a formidable challenge to contemporary medicine and the global economy, not to mention a catastrophic risk to human health. Almost all of these viruses are zoonotic, meaning they were first identified in animals and then spread to humans. An emerging virus may cause only a few isolated instances, resulting in a limited outbreak, or it may cause widespread infection and spread to other parts of the world, triggering a full-blown epidemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Many small molecule inhibitors have been designed to target the proteins important for the life cycle of MPXV, such as the DNA ploymerase, Topisomerase 1, and Cysteine proteinases 49 , 50 . However, these molecules mainly target the catalytic site of the protein, which is largely conserved in the homologous proteins in the host.…”
Section: Discussionmentioning
confidence: 99%
“…Many small molecule inhibitors have been designed to target the proteins important for the life cycle of MPXV, such as the DNA ploymerase, Topisomerase 1, and Cysteine proteinases 49 , 50 . However, these molecules mainly target the catalytic site of the protein, which is largely conserved in the homologous proteins in the host.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, using molecular docking and molecular dynamics simulations, four potential inhibitors—Tipranavir, Cefiderocol, Doxorubicin, and Dolutegravir—were identified as candidates for repurposing against the mpox virus. In a study, Bansal et al [25] tested phytochemicals from Allophylus serratus against core viral cysteine proteases from mpox virus. These compounds included N-(2-Allylcarbamoyl-4-chloro-phenyl)-3,4-dimethoxy-benzamide, 6-Dimethylaminona phthene -1-sulfonicacid amide, and Oleic Acid.…”
Section: Discussionmentioning
confidence: 99%
“…A modelled protein structure of cysteine protease was used in structure-based drug design to screen phytochemicals against the MPXV [53]. This study discussed the application of molecular docking that identified N-(2-Allylcarbamoyl-4-chloro-phenyl)-3,4-dimethoxybenzamide, which exhibited promising molecular binding results.…”
Section: Prediction Of Protein Structurementioning
confidence: 99%